The secular quest for meaning in life: Denton papers in implicit religion - Bailey, Edward I. (Edwin Mellen Press, 2002)
This collection of twenty papers originally contributed to the annual Denton Conferences in Implicit Religion bespeaks, through the range and quality of its contents, the achievement of its editor in gaining currency for the concept of "implicit religion" in a project spanning three decades. As Dr. Bailey immediatly concedes, the concept of implicit religion has been criticized for lacking analytical specificity, transgressing appropriate boundaries and promoting an empirically over-inclusive understanding of religion and spirituality. This volume of Denton Papers in Implicit Religio